2017
DOI: 10.1016/j.jes.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A zero-valent iron and organic matter mixture enhances herbicide and herbicide degradation product removal in subsurface waters

Abstract: The pesticide atrazine, its degradation products, and 2,6-dichlorobenzamide (BAM) are persistent in groundwater environment. We studied whether their dissipation can be enhanced with a mixture of a complex carbon source and zero-valent iron (ZVI) called EHC®. The application rates were 1.0% and 2.0% (by weight) in subsurface sediments slurries (atrazine 30mg/L), and 2.0% in 1.5m pilot-scale sediment columns with groundwater flowing through (atrazine 0.08, desethylatrazine DEA 0.03, BAM 0.02μg/L). In the slurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(43 reference statements)
0
3
1
Order By: Relevance
“…Although iron has been associated with the remediation of some pollutants [17,25], and the sediments of this study naturally contained about 12 mg g −1 of iron, it apparently did not significantly improve the chemical dissipation of colloid-bound atrazine. NH 4 -N and NO 3 -N concentrations below the detection limit suggest that nitrogen limited microbial growth in the sediments, and atrazine was used as the nitrogen source (Table 3).…”
Section: Atrazine-contaminated Aquifer Sediments and Remediationcontrasting
confidence: 56%
“…Although iron has been associated with the remediation of some pollutants [17,25], and the sediments of this study naturally contained about 12 mg g −1 of iron, it apparently did not significantly improve the chemical dissipation of colloid-bound atrazine. NH 4 -N and NO 3 -N concentrations below the detection limit suggest that nitrogen limited microbial growth in the sediments, and atrazine was used as the nitrogen source (Table 3).…”
Section: Atrazine-contaminated Aquifer Sediments and Remediationcontrasting
confidence: 56%
“…Previously, the degradation of atrazine and its major metabolites (DEA and DIA) in water by photocatalytic oxidation under sunlight has achieved good results (Komtchou et al 2018). The use of a carbon source plus zero-valent iron under aerobic conditions can also effectively promote the dissipation of atrazine and DEA at a relatively low pollution level (Kerminen et al 2017). However, different remediation methods vary considerably and are limited by high energy consumption and excessive pollutant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…ATZ has thus been the target of many studies regarding the development of alternative treatment techniques, such as AOPs, biological treatments, new adsorptive materials, zero‐valent metals, among others. Despite this large number of studies, none were found to be dedicated to testing the feasibility of monometallic copper.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although the allowed concentration of ATZ in drinking water is up to 2 μg L −1 16 in Brazil and up to 3 μg L −1 in the United States of America, 17 it is detected above these concentrations in drinking water supplies. 18 ATZ has thus been the target of many studies regarding the development of alternative treatment techniques, such as AOPs, [19][20][21][22][23] biological treatments, [24][25][26] new adsorptive materials, 27 zero-valent metals, 11,[28][29][30] among others. Despite this large number of studies, none were found to be dedicated to testing the feasibility of monometallic copper.…”
Section: Introductionmentioning
confidence: 99%